EU-Swiss trade integration via input-output linkages - Peter H. Egger; Katharina Erhardt (Aussenwirtschaft, 2016)
This paper provides a first assessment of Switzerland's international input-output linkages. In doing so, the paper focuses on Switzerland's trade with the European Union, which rep- resents the country's most important trading partner. In 2015, more than 50% of Swiss exports were directed to the EU while more than 70% of Swiss imports were sourced from EU countries. Using data on Switzerland's transaction-level imports and data on the sector association of a subset of Swiss firms, we are able to characterize the detailed nature of these imports regarding the sectors they are directed to and the countries they originate from.
Keywords: F1; F15; 330; Global value chains; Input-output tables